Quantification of the renal sinus fat and exploration of its relationship with ectopic fat deposition in normal subjects using MRI fat fraction mapping - Zhang, Qin-He; Chen, Li-Hua; An, Qi; Pi, Peng; Dong, Yi-Fan; Zhao, Ying; Wang, Nan; Fang, Xin; Pu, Ren-Wang; Song, Qing-Wei; Lin, Liang-Jie; Liu, Jing-Hong; et al. (Frontiers in Endocrinology, 2023)
Purpose: To determine the renal sinus fat (RSF) volume and fat fraction (FF) in normal Chinese subjects using MRI fat fraction mapping and to explore their associations with age, gender, body mass index (BMI) and ectopic fat deposition. Methods: A total of 126 subjects were included in the analysis. RSF volume and FF, visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) area, and hepatic and pancreatic FFs were measured for each subject. The comparisons in gender were determined using two-tailed t-tests or the nonparametric Mann-Whitney U-test for normally or non-normally distributed data for continuous variables and the chi-square test for categorical variables. Comparisons of RFS volume and FF between right and left kidneys were determined using paired sample t-tests. Multivariable logistic models were performed to confirm whether RSF differences between men and women are independent of VAT or SAT area. When parameters were normally distributed, the Pearson correlation coefficient was used; otherwise, the Spearman correlation coefficient was applied. Results: The RSF volumes (cm3) of both kidneys in men were significantly bigger than those of women (P < 0.05). The RSF FFs (%) of both kidneys in men were significantly higher than those of the women (P < 0.05). The RSF differences between men and women are not independent of SAT area and VAT area (except for right RSF volume). In addition, the RSF volumes and FFs in both kidneys in the overall subjects show significant correlations with age, BMI, VAT area, hepatic fat fraction and pancreatic fat fraction (P < 0.05). However, the patterns of these correlations varied by gender. The RSF volume and FF of left kidney were significantly larger than those of the right kidney (P < 0.05). Conclusions: The RSF volume and FF of both kidneys in men was significantly larger than those of the women. And the RSF volume and FF of left kidney were significantly higher than those of the right kidney. There were significant correlations observed for the RSF volume and FF in both kidneys with BMI, VAT area, hepatic fat fraction and pancreatic fat fraction, but not with SAT area.